2010
DOI: 10.3109/08958378.2010.489074
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function and histological impairment in mice after acute exposure to aluminum dust

Abstract: Along the aluminum refining process, alumina (Al2O3) constitutes the main source of dust. Although aluminum refinery workers present respiratory symptoms with lung functional changes, no conclusive data about lung function impairment after alumina exposure has been so far reported. We examined the pulmonary alterations of exposure to material collected in an aluminum refinery in Brazil. BALB/c mice were exposed in a whole-body chamber for 1 h to either saline (CTRL, n = 11) or to a suspension (in saline) of 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…If a similar response is present in aluminium production workers is, to our knowledge, not yet studied. However, in an experimental whole-body chamber study of mice exposed to an atmospheric concentration of 8 mg/m 3 dust from an aluminium-producing facility, a significant increase in alveolar collapse and increased level of percentage of neutrophils in the lung parenchyma was observed 29. This Al 2 O 3 dust also contained a mixture of other substances such as mercury, cadmium, chromium, copper, iron, manganese, nickel, zinc and lead.…”
Section: Discussionmentioning
confidence: 97%
“…If a similar response is present in aluminium production workers is, to our knowledge, not yet studied. However, in an experimental whole-body chamber study of mice exposed to an atmospheric concentration of 8 mg/m 3 dust from an aluminium-producing facility, a significant increase in alveolar collapse and increased level of percentage of neutrophils in the lung parenchyma was observed 29. This Al 2 O 3 dust also contained a mixture of other substances such as mercury, cadmium, chromium, copper, iron, manganese, nickel, zinc and lead.…”
Section: Discussionmentioning
confidence: 97%
“…There have been no epidemiological studies of intentionally manufactured aluminum oxide nanomaterials. However, there have been occupational studies that have shown that inhaled aluminum oxide particles (size unspecified) are linked to pulmonary fibrosis, asthma, chronic obstructive lung diseases and possibly lung cancer (49)(50)(51)(52). Ultrafine particles have been identified in primary aluminum smelters and pot rooms (53).…”
Section: Aluminum Oxidementioning
confidence: 99%
“…In the physiological conditions of human beings, 50 % of this metal is accumulated in the skeletal system and 25 % in the lung tissue (ATSDR 1999). Aluminum might potentiate oxidative and inflammatory stress leading to functional disturbance in the lung epithelium (Mazzoli-Rocha et al 2010). Chronic Al administration might be responsible for the oxidative cell damage due to its interference with the mitochondrial functions disturbing the redox status (Kumar et al 2009).…”
Section: Introductionmentioning
confidence: 98%